Accuracy assessment of speed values calculated from GNSS tracks of roads obtained from VGI. Issue 367 (4th July 2019) - Mozas-Calvache, Antonio Tomás
Abstract : This study describes the results of an assessment of the accuracy of relative measures between two points, and more specifically of speed values, obtained from Global Positioning Satellite Systems (GNSS) tracks acquired by contributors of Volunteered Geographic Information (VGI). The VGI does not usually include information about the positional accuracy of the trackpoints neither of speed values derived from these positions. Consequently, the assessment is based on a field test that consisted of a vehicle which travelled a highway with a set of Global Positioning System (GPS) devices like those commonly used by VGI contributors. These devices captured positions of trackpoints with a time interval of 1 second. Additionally, a more accurate geodetic RTK–GNSS receptor controlled these positions. The paper describes the methodology employed, taking into account several parameters such as the acquisition time interval, the accuracy of control positions, etc. The results have demonstrated the viability of the methodology applied, the possible use of VGI in order to determine the speed values of the trackpoints and the possible improvement in the accuracy achieved with the increase of the distance between trackpoints (and as a consequence of time interval), but with the disadvantage of a reduction in the quantity of trackpoints. Thus, several values of time intervals have been suggested, considering the accuracy required.